Private wrongs - Ripstein, Arthur (Harvard University Press, 2016)
From the perspective of prominent positions in both moral philosophy and legal scholarship, tort law can seem baffling: people are made to pay damages when they are barely or not at fault, yet some serious harms go uncompensated. Many of these puzzles grow out of the assumption that the law's concern must either be to compensate losses or penalize misconduct. In private wrongs, Arthur Ripstein provides a philosophical and systematic account of the rights protected by tort law. The law of tort protects what people already have: their person, understood as bodily integrity and reputation, and property. Ripstein articulates the form of these rights, and provides a simple but compelling explanation of the sense in which the point of damages is to make it as if the wrong had never happened. He explains why this matters even though damages are at best an imperfect substitute and why enforcing private rights is consistent with the other activities of a liberal state without being reducible to them.--Publisher's information.